Calf growth, milk offtake and estimated lactation yields of Borana cattle in the southern rangelands of Ethiopia - Nicholson, M.J. (International Livestock Centre for Africa, 1983)
Presents results of a statistical analysis of data on 133 Borana calves & 8 cows to determine average birth weight, body weight at various ages, growth rates & growth curves of calves and milk offtake (milk taken for human use) and to estimate milk yield of cows (by adding milk offtake & milk intake of calves) at various localities in the southern Rangelands, Ethiopia; w. data on milk composition of Borana cows.